Influence of residual stress on the sliding wear of AISI 4340 steel - Tomaz,Ítalo do Valle (2020)
ABSTRACT Mechanical components and structures wear out as a result of friction between surfaces in relative motion. Residual stresses play an important role for the tribological performance of components since compressive residual stresses yield positive effects on wear resistance. However, the real effect of residual stresses on the tribological performance of surfaces is not entirely clear. The objective of this work is to evaluate the residual stress behavior during a pin-on-disk wear test of quenched and tempered AISI 4340 disk specimens against a counter-body of steel AISI E 52100. Tests were performed in shot peened and non-shot peened specimens in six steps and residual stresses were evaluated after each one by X-ray diffraction technique using sin2y method. The results shown that wear rate of the shot peened specimens was approximately fifty percent lower. Shot peening induced compressive residual stresses contributed to this effect even though they were modified during the pin-on-disk test.